2010
DOI: 10.1111/j.1365-2591.2010.01735.x
|View full text |Cite
|
Sign up to set email alerts
|

Digital subtraction radiography evaluation of the bone repair process of chronic apical periodontitis after root canal treatment

Abstract: Digital subtraction radiography is a useful method for evaluating the progress of bone repair after root canal treatment. Noticeable mineral gain was observed approximately 90 days after root canal filling and definite bone repair after 180 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
0
11
0
4
Order By: Relevance
“…In the 1980s, the introduction of subtraction radiography enabled the visualization of bone changes and allowed reliable monitoring of density changes in different clinical situations. 13 Benfica e Silva et al 13 used the "digital subtraction radiography" software to perform the radiographic subtraction technique to evaluate the bone healing process of chronic periapical lesion after root canal treatment. The results showed that, by analyzing the intensity of the pixels and their gray tones, the method could determine the progress of apical healing.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1980s, the introduction of subtraction radiography enabled the visualization of bone changes and allowed reliable monitoring of density changes in different clinical situations. 13 Benfica e Silva et al 13 used the "digital subtraction radiography" software to perform the radiographic subtraction technique to evaluate the bone healing process of chronic periapical lesion after root canal treatment. The results showed that, by analyzing the intensity of the pixels and their gray tones, the method could determine the progress of apical healing.…”
Section: Discussionmentioning
confidence: 99%
“…DSR has been used both in vitroand in clinical studies as a sensitive tool to monitor minor bone changes, including mineral loss and gain. [9][10][11][12][13][14][15][16][17][18] The DSR method is based on the digital alignment and superimposition of two radiographs of the same region obtained at different time. 19 A subtracted image is produced using a specific software system algorithm that converts the two radiographic images into a homogeneous grey background of 128 pixels.…”
Section: Introductionmentioning
confidence: 99%
“…Unchanged regions present grey pixel values close to 128, while higher values indicate mineral density gain and lower values are compatible with density loss. [17][18][19][20] DSR is commonly used for different purposes in dentistry and subtracted images can be obtained from conventional or digital radiographs. These two-dimensional images of three-dimensional structures can provide only limited information about a region of interest, due to superposition, inherent to bidimensional radiographs, which leads to a limited three-dimensional visualization at different depth levels.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst subtraction radiography facilitates assessment of periapical bone tissue changes over time, it has been tested in only a few clinical follow‐up studies (Nicopoulou‐Karayianni et al. 2002, Benfica e Silva et al. 2010).…”
Section: Introductionmentioning
confidence: 99%